Listen NCERT Audio Books to boost your productivity and retention power by 2X.

12

Find x, if

(i)

(ii)

(iii)

(iv)

(v)

(vi)

(i)

[Using ^{n} × ^{m} = ᵐ⁺^{n}]

Equating coefficients when bases are equal.

(ii)

[Using ^{n} ÷ ^{m} = ᵐ^{–n}]

Equating coefficients when bases are equal.

(iii)

[Using ^{n} × ^{m} = ᵐ⁺^{n}]

Equating coefficients when bases are equal.

(iv)

[Using ^{n} × ^{m} = ᵐ⁺^{n}]

Equating coefficients when bases are equal.

(v)

[Using ^{n} ÷ ^{m} = ᵐ^{–n}]

Equating coefficients when bases are equal.

(vi)

[Using ^{n} × ^{m} = ᵐ⁺^{n}]

Equating coefficients when bases are equal.